GENETIC AND IMMUNOLOGICAL PHENOTYPES OF REACTIVE ARTHRITIS: A PERSONALIZED DIAGNOSTIC MODEL (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Reactive arthritis (ReA) is an inflammatory joint disease that develops as a sterile immune-mediated response following certain genitourinary or gastrointestinal infections. Unlike septic arthritis, reactive arthritis is characterized by the absence of viable pathogens within the affected joints, underscoring its immunopathological rather than infectious nature. Clinically, ReA is often associated with asymmetric oligoarthritis, enthesitis, axial involvement, and extra-articular manifestations affecting the eyes, skin, and mucosal surfaces. Despite its well-recognized clinical spectrum, reactive arthritis remains a diagnostically challenging condition due to its heterogeneous presentation and variable disease course.